Synthesis and antimicrobial evaluation of promising 7-arylamino-5, 8-dioxo-5, 8-dihydroisoquinoline-4-carboxylates and their halogenated amino compounds for treating Gram-negative bacterial infections. Issue 30 (27th March 2017) - Novais, Juliana S.; Campos, Vinicius R.; Silva, Ana Carolina J. A.; de Souza, Maria C. B. V.; Ferreira, Vitor F.; Keller, Vitor G. L.; Ferreira, Matheus O.; Dias, Flaviana R. F.; Vitorino, Maíra I.; Sathler, Plínio C.; Santana, Marcos V.; Resende, Jackson A. L. C.; et al.
Abstract : In this work we described the synthesis and antimicrobial evaluation of 7-arylamino-5, 8-dioxo-5, 8-dihydroisoquinoline-4-carboxylates derivatives that exhibited remarkable activity against two Gram-negative strains of clinical importance. Abstract : Pathogenic bacteria may cause serious infections, such as pneumonia, which can be fatal especially to immunosuppressed individuals. Hospitalized patients are particularly susceptible to antibiotic-resistant infections, which are worsened when caused by resistant Gram-negative pathogens due to there being few therapeutic options available. Thus, this work describes the synthesis and in vitro antimicrobial profile of 7-arylamino-5, 8-dioxo-5, 8-dihydroisoquinoline-4-carboxylates and their halogenated aminoquinones against Gram-positive and Gram-negative bacteria. Interestingly, these bioactive substances have shown promising activity against Gram-negative pathogenic strains. Among these derivatives, two non-halogenated amino compounds exhibited promising MIC and MBC values (MIC = MBC = 1–2 μg mL −1 ) against Escherichia coli ATCC 25922 and Pseudomonas aeruginosa ATCC 27853, two Gram-negative strains of clinical importance. In addition, mono- and di-brominated aminoquinones were also effective in preventing the growth of E. coli (MIC = MBC = 2–4 μg mL −1 ). The in vitro hemocompatibility evaluation showed a low toxicity profile for the active aminoquinones in hemolysis assays. These results suggest that these substances have potential for exploring the design of new antimicrobial prototypes against Gram-negative bacteria.